Studies in church history - Parsons, Reuben (F. Pustet, 1896)
v. 1. Centuries I.-VIII -- v. 2. Centuries IX.-XIV -- v. 3. Centuries XV.-XVI -- v. 4. Centuries XVII.-XVIII -- v. 5. Century XIX, pt. I -- v. 6. Century XIX, pt. II.